Active Ageing Good Practices Promoting Intergenerational Communication and Understanding - Maria Aurora, Fenech; Edel Borg, Mizzi (Magyar Gerontológia, 2023)
Persistent negative stereotypes on the aging process and the older person are noticeable within the current youth-orientated culture. Older persons may also hold negative stereotypes about the younger generation. These undesirable typecasts co-exist because younger and older persons often have limited contact with each other. Indeed, the younger generation, only gets to engage in communication with the older person within the family unit, rarely outside their own familial structures. Similarly, older persons, residents of long-term care have limited opportunities of interacting with the younger generation.